Avaliação da presença de osteopatia decorrente do diabetes tipo 1 em crianças e adolescentes do Rio Grande do Norte - Loureiro, Melina Bezerra (2008)
Diabetes Mellitus (DM) and osteoposes are chronic diseases with great socioeconomic consequences, mainly due to the late complications and consequent disabilities. The potential effects of DM on bone metabolism remain a very conroversial issue, and disagreement exists with regard to the clinical implications of diabetic osteopenia and the mechanism of its ocurrence. The issue is further complicated by the contribuicion of the especific factors, such as duration of disease an dthe degree of metabolic control. The objective of this study is to identify the osteopathy in children and adolescents with DM 1 assisted in the hospital of pediatrics, UFRN, through biochemical markers of bone and mineral metabolism and the extent of bone mineral density. The study was composed by 74 diabetics type 1 patients (DM1) of both gender and aged 6 to 20 yars. Normoglicêmic group was composed by 97 healthy subjects of both genders, which showed the same age range of DM1, in addition to same socioeconomic class. These individuals qere students from the networks of public education in the city of Natal-RN, randomly invited to paticipate in our study. Both groups DM1 and NG were divided intofour subgroups, according to the classification of tanner , T1, T2, T3, T4 for achieving a benchmark. Diabetic individuals showed up with a poor glycemic control. the group DN1 T4 showed an incresead value for total protein, albumin, urea and microalbumiuria are predictors of grumelura injury in DM1 patients . The total alkaline phosphatase activitywas kept on high levels for both groups because they are in a stature development age. For osteocalcin there were decreased levels for groups Dm1 T1, T2, and T3 when compared to their NG (s), suggesting that this decrease could be associated with reduction in the number and/or differentiation os osteoblasts thereby contributing to reducing bone formation. There were no changes in the activity of TRAP. The serum concentrations of total and ionized calcium, phosphorus and magnesium were included within the RV. It was observed that the BMD (Z- SCORE ) has always been within the RV for both groups, despite to DM1 T4. Taking all together, our results support the hypothesis that children and adolescents with type 1 DM present the risk in the long run to suffer a reduction in the bone mass, associated to poor glicemic control and disease duration. It could limit the bone growth and increase the probality of development of osteopenia, as well as other complications surch as retinopathy and renal failure